Does autonomous moral reasoning favor consequentialism? - Turan, Caner (Estudios de Filosofía, 2022)
This paper addresses an important issue that has been commonly debated in moral psychology, namely the normative and metaethical implications of our differing intuitive responses to morally indistinguishable dilemmas. The prominent example of the asymmetry in our responses is that people often intuitively accept pulling a switch and deny pushing as a morally permissible way of sacrificing an innocent person to save more innocent people. Joshua Greene traces our negative responses to actions involving “up close and personal” harm back to our evolutionary past and argues that this undermines the normative power of deontological judgments. I reject Greene’s argument by arguing that our theoretical moral intuitions, as opposed to concrete and mid-level ones, are independent of direct evolutionary influence because they are the product of autonomous (gene-independent) moral reasoning. I then explain how both consequentialist and deontological theoretical intuitions, which enable us to make important moral distinctions and grasp objective moral facts, are produced by the exercise of autonomous moral reasoning and the process of cultural evolution. My conclusion will be that Greene is not justified in his claim that deontology is normatively inferior to consequentialism.